Spiritual Emotional Freedom Technique (Seft) untuk Mengurangi Kecemasan pada Orang Tua yang Anaknya Menjadi Korban Pelecehan Seksual - Ardian Adi Putra (Universitas Islam Indonesia, 2015)
This research aims to examine the effectivity of SEFT in reducing the anxiety of the parents with child sexual abuse. SEFT is especially imposed on the anxiety symptoms which can be consciously felt by the research subject. The subjects are two parents, who have children experiencing sexual abuse.The research used pre-experimental design; One-shoot case study.The SEFT treatment was given to reduce the anxiety symptoms.Based on the interview and observation results, the anxiety symptoms were decreased after the given intervention.Keywords: SEFT, Anxiety, Parents with child sexual abuse